The value of plasma insulin-like growth factor 1 and interleukin-18 in the diagnosis of bronchopulmonary dysplasia in premature infants - Huang, Lie; Guo, Ning; Cheng, Meile; Wang, Jianhui; Chen, Feifan; Shi, Yuan (Frontiers in Pediatrics, 2022)
Objective: To explore the diagnostic value of IGF-1 and IL-18 in premature infants with BPD. Methods: Through a prospective observational study, the serum samples of infants in the BPD group and the non-BPD group were collected at different targeted time points, and the serum IGF-1 and IL-18 concentrations were dynamically monitored by ELISA. The Student t-test and one-way analysis of variance were adopted to analyze data, and the receiver operating characteristic (ROC) curve was used to test the diagnostic value.Result: A total of 80 VLBW premature infants admitted to NICU between January 2020 and 2021 were finally included. Compared with the non-BPD group, infants diagnosed with BPD had a significantly lower serum concentration of IGF-1 (P<0.05) but a higher level of IL-18 (P<0.05) on days 1, 7, 14, and 28 after birth. With the ROC curve analysis, the serum concentration IGF-1 on day 14 and IL-18 on day 28 reported high sensitivity and specificity to predict the risk of BPD (IGF-1: sensitivity: 91.67%; specificity: 81.82%; AUC: 0.9261; IL-18: sensitivity: 91.67%; specificity: 81.86%; AUC: 0.823). And more substantial predictive power was found in the combination of IGF-1 on day 14 and serum IL-18 on day 28: the sensitivity was 94.4% and the specificity was 91.6%, with the AUC of 0.969. Conclusion: IGF-1 and IL-18 might be closely involved in the occurrence and development of BPD. The serum concentration of IGF-1 combined with IL-18 could be potentially sensitive markers for the early diagnosis and severity of BPD.